Penggunaan Media Smartboard dalam Meningkatkan Pemahaman Siswa pada Pelajaran PAI di SD Prestige Bilingual School - Aini, Putri Rizki; Yuliyani, Yuliyani; Pratama, Reza (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This research wants to discuss various problems in the world of education, namely that many educators still use conventional media such as lecture or question and answer methods which result in learning being inactive, thus affecting the quality of learning outcomes. This research aims to see how the role of using smartboard media in the learning process can improve students' understanding, especially in Islamic studies. Researchers used observation, interviews and documentation methods. The results of this research show that the presence of smartboards at Prestige Bilingual School in the teaching and learning process in Islamic studies has a positive impact, where smartboards become an attraction to provide a feeling of joy and comfort, thereby encouraging students to learn, which of course can increase understanding and strengthen students' memories of Islamic Religious Lessons. Like humans who are not perfect, this smartboard media also has its drawbacks, namely that the price is relatively expensive, making some school institutions think again about using it, as well as technicians who are still rarely found. The educators here have not received special training to master smartboards so not all educators use smartboard media in the learning process at school and this smartboard requires electricity, if it goes out then it cannot be run. Keywords: Smartboard Media; Student Understanding; Islamic Education Lessons